2008
DOI: 10.3748/wjg.14.2888
|View full text |Cite
|
Sign up to set email alerts
|

Serum leptin and soluble leptin receptor in non-alcoholic fatty liver disease

Abstract: feature of steatosis, and serum leptin seems to increase as hepatocyte steatosis develops. An enhanced release of leptin is accompanied by an decrease in sOB-R concentration, which suggests higher resistance of peripheral tissues towards the action of leptin. INTRODUCTIONLeptin -the ob gene product -is a circulating 16-kDa peptide hormone secreted mainly by adipocytes of white fat tissue. It regulates food intake, body fat, insulin action, thermogenesis, induction of angiogenesis, and modulation of the immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 33 publications
(28 reference statements)
5
40
0
3
Order By: Relevance
“…In the setting of obesity, the body becomes resistant to the effects of leptin, resulting in paradoxical weight gain in the setting of high levels of circulating leptin (10). It has been shown that there is strong negative correlation between serum levels of leptin and leptin receptor in patients with non-alcoholic fatty liver disease (11). These findings point out to insulin resistance as a potentially independent risk factor for melanoma (12).…”
Section: Resultsmentioning
confidence: 65%
“…In the setting of obesity, the body becomes resistant to the effects of leptin, resulting in paradoxical weight gain in the setting of high levels of circulating leptin (10). It has been shown that there is strong negative correlation between serum levels of leptin and leptin receptor in patients with non-alcoholic fatty liver disease (11). These findings point out to insulin resistance as a potentially independent risk factor for melanoma (12).…”
Section: Resultsmentioning
confidence: 65%
“…Conversely, the circulating levels of adiponectin are inversely proportional to body fat content and become reduced in patients with NAFLD. [38][39][40][41] Oxidative stress and mitochondrial dysfunction play a wellreported role in NASH, with a direct correlation between the degrees of oxidative stress and the severity of liver disease. Structural mitochondrial abnormalities and impairment of mitochondrial respiratory chain activity have been reported in human studies.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Leptin receptor is a member of the class-1 cytokine receptor family and it is an important determinant of leptin sensitivity originally found in hypothalamic neurons. However, alongside the membrane-bound forms of this receptor, there is also a soluble form in plasma (1). The function of this soluble form is not known yet, but it is thought to contribute to the delay in clearance of leptin (3).…”
Section: Introductionmentioning
confidence: 99%
“…An inverse relationship was found between leptin and soluble leptin receptor levels (4). The balance between bound and free leptin depends on the plasma concentration of this soluble leptin receptor (1,5). The ratio between total and soluble leptin concentration was used as the free leptin index, indicating leptin resistance (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation